2010
DOI: 10.1002/chem.201000161
|View full text |Cite
|
Sign up to set email alerts
|

Chirally Functionalized Hollow Nanospheres Containing L‐Prolinamide: Synthesis and Asymmetric Catalysis

Abstract: Chirally functionalized hollow nanospheres with different surface properties were successfully synthesized by co-condensation of (2S,1'R,2'R)-N-tert-butyloxycarbonylpyrrolidine-2-carboxylic acid [2'-(4-trimethoxysilylbenzylamide)cyclohexyl] amide with 1,2-bis(trimethoxysilyl)ethane or tetramethoxysilane using F127 (EO(106)PO(70)EO(106)) as surfactant in water. The TEM and N(2) sorption characterizations show that the particle size of the hollow nanosphere is 15-21 nm with a core diameter of 10-16 nm. These L-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Yang et al developed the general methods to fabricate HSNs based on F127-NaH 2 PO 4 -Na 2 HPO 4 and F127-TMB systems (F127: EO 106 PO 70 EO 106 ; TMB: mesitylene). [31][32][33][34][35][36][37] The assembly of the silicate species around the corona of individual micelle results in the formation of nanospheres with a hollow interior after removal of the surfactant by extraction or calcination. The particle size of the HSNs is in the range of 12-30 nm.…”
Section: Soft Templating Routementioning
confidence: 99%
“…Yang et al developed the general methods to fabricate HSNs based on F127-NaH 2 PO 4 -Na 2 HPO 4 and F127-TMB systems (F127: EO 106 PO 70 EO 106 ; TMB: mesitylene). [31][32][33][34][35][36][37] The assembly of the silicate species around the corona of individual micelle results in the formation of nanospheres with a hollow interior after removal of the surfactant by extraction or calcination. The particle size of the HSNs is in the range of 12-30 nm.…”
Section: Soft Templating Routementioning
confidence: 99%
“…Among the silica fibers, spheres, rods and nanoparticles, the hollow nanospheres are very attractive, given that the hollow interior can encapsulate the guest molecules for wide application potentials [19][20][21][22][23][24][25][26][27][28]. The modification of the shell of the hollow nanospheres may further expand the application potentials of the hollow nanospheres [29][30][31][32][33][34][35]. The strategies for the synthesis of hollow silica-based nanospheres were already well reviewed [36,37], and can be categorized as: selective etching or dissolution, soft templating, self templating, galvanic replacement method, and Ostwald ripening method, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Recently, we also found that the catalytic activity of a chiral prolinamide catalyst that was supported on hollow nanospheres increased sharply with increasing surface hydrophobicity after surface passivation. [17] The surface passivation of a silica-supported BINOLÀTi (BINOL = 1,1'-bi-2-naphthol) catalytic system has been used to afford highly efficient catalysts. [18][19][20][21][22] Chen and co-workers prepared a new type of superhydrophobic material, in which a Co-incorporated SiO 2 nanocomposite was functionalized with organic groups, by surface passivation.…”
Section: Introductionmentioning
confidence: 99%